Outward foreign direct investment by emerging market firms: A resource dependence logic - XIA, Jun (Institutional Knowledge at Singapore Management University, 2014)
This study examines and extends the resource dependence logic of diversification for a better understanding of outward foreign direct investment (OFDI) activities by emerging market firms. We contend that the diversification logic is bounded by state ownership, an important but less considered component of interdependence. Our empirical results, based on panel data analysis of Chinese listed firms, suggest that the level of interdependence between Chinese and foreign firms in China in multiple forms, including symbiotic, competitive, and partner interdependencies, is positively associated with the level of the Chinese firms' OFDI activities. However, Chinese firms with higher levels of state ownership are less susceptible to the pressures imposed by foreign firms to invest abroad.